STUDY ON THE IMPACT OF STRATEGIC MOVES AND ENERGIES OF A BUSINESS LEADER ON THE TECHNOLOGY INNOVATION OF AN ORGANISATION - Arun, C. Joe (Digital Repository of Theses, 2023)
Purpose There is a gap in the literature on the impact of leadership behaviour on organisational outcomes in general and technology innovation in particular. Further, the literature review has shown ample proof of the existence of eight strategic moves and energies of a business leader which to a greater extent determines his / her leadership competence. There is a lack of studies on the impact of these moves and energies on the level of technology innovation in an organisation. Furthermore, the impact of these moves and energies on leader attractiveness is not empirically established so far. Hence, the present study aims to understand the impact of the strategic moves and energies of a business leader on the technology innovation of an organisation. Design /Methodology The study is based on primary data collected from a targeted sample of 600 respondents. A theoretical model has been developed based on the existing literature on anthropology, personnel management and innovation. The snowball and convenience sampling techniques were adopted for the study, and the required data were collected using a well-structured and pre-tested questionnaire. PLS-SEM analysis has been used to assess the theoretical model of the study. vi Findings The study established that historical consciousness, sense of future, authority, attitude, output and transcendence are the significant factors affecting leader attractiveness in an organisation. Leader attractiveness and authority are the only two variables that have a significant impact on technology innovation. The mediation analysis shows the existence of partial complementary mediation of leader attractiveness on historical consciousness, sense of future, authority, attitude, output and transcendence, in their relationship with technology innovation. The structural model has achieved a moderate-to-high level of success in explaining the impact of the business moves and strategies of a business leader on the technology innovation of an organisation. The Important-Performance Map Analysis (IPMA) has shown that leader attractiveness is the most significant factor affecting the technology innovation of an organisation. If 1 unit of performance of leader attractiveness increases from 46.731 to 47.731, then technology innovation will increase from 49.503 to 49.737. This is the highest increase in the performance of our target variance, that is, technology innovation. Research Limitations The study is limited to respondents in the major cities of India and due to the paucity of resources and also because of the nature of the study, snowball and convenience sampling have been adopted. Further, the study measures the impact of the strategic moves of a business leader only from the perception of the employees. Hence, future studies can explore the insight of business leaders on the rationale behind their strategic moves and energies and their perception of how attractive they are among their employees.